Bioprospection of yeasts as biocontrol agents against phytopathogenic molds - Rosa-Magri, Márcia Maria; Tauk-Tornisielo, Sâmia Maria [UNESP]; Ceccato-Antonini, Sandra Regina (Brazilian Archives of Biology and Technology, 2011)
Yeasts isolated from sugar cane and maize rhizosphere, leaves and stalks were screened against the phytopathogenic molds Colletotrichum sublineolum and Colletotrichum graminicola, both causal agents of the anthracnose disease in sorghum and maize, respectively. Strains identified as Torulaspora globosa and Candida intermedia were able to inhibit the mold growth, with the first species also exhibiting killer activity. No previous report on the application and potentiality of these yeasts as biocontrol agents were found neither the killer phenotype in Torulaspora globosa.
Keywords: bioprospection; Colletotrichum graminicola; Colletotrichum sublineolum; killer activity; mycocinogenic